Use of organic polymers for improvement of coking potential of poor coking coal. Issue 7 (2nd July 2020) - Nag, Debjani; Karmakar, Shilpi; Burgula, Laxminarayana; Dash, J.; Dash, P.S.; Ghorai, S.
ABSTRACT: As the reserve of prime coking coal is low, there is a good amount of research going on worldwide to improve the coking potential of non-coking coal. Researchers have revealed the importance of hydrogen generation/transfer to improve the coking potential of coal. Based on this hypothesis, in this paper, the authors have tried to improve the coking potential of non-coking coal by adding different polymers. The polymers are derived from formaldehyde and phenol derivatives. Coking potential has been tested through conventional tests like crucible swelling number. Thermogravimetric mass spectroscopy (TG-MS) has been used to get an idea of plasticity and hydrogen generation in the plastic zone. High-temperature microscopy has also been used to evaluate the swelling of coal. Results indicate that the addition of polymers in a small percentage has an effect on hydrogen generation in the plastic zone, and thus, it can improve the coking potential of non-coking coal.